Sosialisasi Dalam Menghindari Jamu Yang Mengandung Bahan Kimia Obat (BKO) - Rahmadani, Rahmadani; Gunawan, Catur; Zhahera, Ghina; Octavia, Mutia; Sunnah, Nehayatul; Rahman, Riyaldi Arian (Universitas Merdeka Pasuruan, 2022)
Jamu is very well known by the wider community so that it is used in self-care measures for body health and maintaining immunity while self-care measures for body health and keeping immunity stable. The need for herbal medicine is increasing in the community as an opportunity for irresponsible people to add medicinal chemicals to herbal medicine. The Food and Drug Supervisory Agency of the Republic of Indonesia (DSA RI) for the period July 2021 to September 2021 has found as many as 53 traditional medicinal products containing medicinal chemical, even though there has been a ban from DSA RI on the use of medicinal chemical in traditional medicine. Analysis of the problem with the interview method to determine the level of knowledge of students about medicinal chemicals and evaluated using a questionnaire. From the results of interviews, 17 students out of 20 students did not know the medicinal chemicals in herbal medicine. Based on the results of the evaluation showed an increase in the percentage of the results of the questionnaire in describing the level of student knowledge.